Peningkatan Produktivitas dan Daya Saing Produk UMKM melalui Transformasi Digital - Widowati; Titik Ekowati; Adhy, Satriyo (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
The development of the digital age today is developing very rapidly. One aspect that has an impact on the development of digital is micro, small, and medium-sized enterprises (UMKM) in Kelurahan Rowosari Prefecture, Tembalang, the city of Semarang. The UMKM in Kelurahan Rowosari has several products that are processed on a domestic scale; one of its products is chips, padi scrubbing, banana bread, and others. The output of the UMKM Kelurahan Rowosari is managed directly by the community that has previously been registered in the Rowosari Keluradan UMKM. The vendor's way of opening stores and receiving orders from customers, as well as the production tools used, are still simple and use the process manually. Besides, the operators are not synergistic and integrated, so the productivity rate is low and less effective. Another obstacle is the limited knowledge of UMKM enterprises in marketing and the fact that they have not applied appropriate technology and information technology to market their products. The target reach of this dedication activity is to increase output and compete with other producers by leveraging digital transformation to expand the market area through online media. Besides, the entrepreneur has the ability to conduct transactions and communicate with customers.